2017
DOI: 10.21042/amns.2017.1.00016
|View full text |Cite
|
Sign up to set email alerts
|

Odd mean labeling for two star graph

Abstract: In this paper further result on odd mean labeling is discussed. We prove that the two star G = K 1,m ∧ K 1,n is an odd mean graph if and only if |m − n| ≤ 3. The condition for a graph to be odd mean is that p ≤ q + 1, where p and q stands for the number of the vertices and edges in the graph respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…Triethylamine (3.97%) is widely used in manufacturing medicines, pesticides, polymerization inhibitors, high-energy fuels, vulcanizing agents of rubber, and so forth [39]. It should be noted that the content of Lupeol (5.20%) in the phenyl alcohol extract of quercetin leaves reaches 5.20%, which has significant effects on anti-tumor, anti-inflammatory, and antioxidant effects [40][41][42].…”
Section: The Gc-ms Analysismentioning
confidence: 99%
“…Triethylamine (3.97%) is widely used in manufacturing medicines, pesticides, polymerization inhibitors, high-energy fuels, vulcanizing agents of rubber, and so forth [39]. It should be noted that the content of Lupeol (5.20%) in the phenyl alcohol extract of quercetin leaves reaches 5.20%, which has significant effects on anti-tumor, anti-inflammatory, and antioxidant effects [40][41][42].…”
Section: The Gc-ms Analysismentioning
confidence: 99%
“…Then, π = {R i : i = 1, 2..., m + 4} is a partition of V(C m n ) and c : V(C m n ) −→ {1, 2, ..., m + t} defined by c(x i ) = j for any x i ∈ R j is a locating coloring of C m n . (2) For n = q(m + 1) + i, where 3 ≤ i < t let R 1 , R 2 , ..., R m+4 similar to the case n = q(m + 1) + 2. Set R m+j = {x (m+1)q+(j−2) }, 5 ≤ j ≤ i + 2.…”
Section: Proofmentioning
confidence: 99%
“…(1) If x n ∈ R m+1 , then c π (x n ) = c π (x m+1 ). (2) If x n ∈ R l , l ≥ m + 2 and x n−1 ∈ R k , where k = m or m + 1. Then, (T\{x 2m+1 }) ∩ R i = φ for all i ≥ m + 3 and i = l. However, k = m, which gives N(x k ) = ({x n , x 1 , x 2 , ..., x m+2 }\{x m }) ∪ (T\{x 2m+1 }) and k = m + 1, which gives N(x k ) = ({x 1 , x 2 , ..., x m+2 }\{x m+1 }) ∪ T, while N(x n−1 ) = {x 1 , x 2 , ..., x m−1 } ∪ (S 2 \{x n−1 }).…”
Section: (6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that, as the CARS-PLS model was based on the optimal key variables, it only used 15.6% of variables in the original information. In this way, the number of variables was reduced [13]. Moreover, the CARS-PLS model could more accurately predict the SSC content in Yali pear than the full-variable PLS model.…”
Section: Introductionmentioning
confidence: 99%